Treatment of intertrochanteric fracture with DHS - M Bahrami (Babol University of Medical Sciences, 2003)
Background and Objective: Intertrochanteric fracture, which occurs in intertrochanteric line, is very common among elderly ages with slight and severe trauma. There are several forms of treatment of this fracture. The aim of this study was to evaluate the treatment of these fractures by DHS in Babol. Methods: This study was conducted on 100 patients (55% male, 45% females) with intertrochanteric fractures referred to the hospitals of Babol town during 1997-2002. The age ranged between 45 to 85 years and patients with fracture of other limbs were excluded. All individuals were operated by DHS and followed up for one year. Findings: 55% and 45% of cases had unstable and stable fractures, respectively. After surgery, complication occurred in 12% of patients, and 30% of cases were died after discharge from the hospital. Eighty-eight of cases were treated by DHS and the results of treatment were satisfactory. This success was equal between sexes. Conclusion: According to the results, this method in treatment of intertrochanteric fracture in comparison to other methods was satisfactory. Therefore, it is suggested all patients with this kind of fracture be treated by DHS.